Encyclopedia of geographic information science - Kemp, Karen K. (Karen Kathleen) 1954-.; Gale Group (Thousand Oaks, Calif. Sage Publications, 2008)
Covers the essence of this new field in an easily understood but detailed style. Includes contributions from some of the best recognized scholars in GIScience, as well as contributions from experts in GIS' supporting disciplines who explore how their disciplinary perspectives are expanded within the context of GIScience.
Editorial board -- List of entries -- Reader's guide -- About the editor and advisory board -- Contributors -- Introduction -- A-Z -- Index.
Electronic reproduction.
Keywords: Geographic information systems -- Encyclopedias; Geospatial data -- Encyclopedias; Electronic books